A Wideband 1 bit 12 × 12 Reconfigurable Beam-Scanning Reflectarray: Design, Fabrication, and Measurement - Han, Jiaqi; Li, Long; Liu, Guangyao; Wu, Zhao; Shi, Yan (IEEE antennas and wireless propagation letters, 2019)
In this letter, a wideband 1 bit 12 × 12 reconfigurable beam-scanning reflectarray is designed, fabricated, and measured. The 1 bit reconfigurable element is realized by soldering PIN diode into a slotted metallic square patch. To enhance the bandwidth of 1 bit reconfigurable reflectarray, we choose the central frequency at 5.0 GHz whose phase shift is 200° where the maximum phase shift occurs. Phase difference within 180° ± 20° is realized from 4.7 to 5.3 GHz. Utilizing this wideband element, the 12 × 12 reconfigurable reflectarray antenna is fabricated and measured. A control board that can display phase shift distributions in real time is designed to regulate all PIN diodes independently. Experimental results show that beam scanning within ±50° can be achieved both in xoz and yoz plane at 5.0 GHz. Also, the measured results present that −1 dB gain bandwidth is 8.4% from 4.85 to 5.275 GHz.